“动宾带宾”在马来西亚华语书面语中的使用考察 = A study of VO1+O2 in written Malaysia Mandarin - 刘昱彤 Lew, Yu Tong (Nanyang Technological University, 2023)
“动宾带宾”是汉语中一个较为特殊的语法现象。当前学界关于该现象的研究主 要集中于中国大陆普通话，较少关注其在其他汉语变体的使用情况和特点。本文以马来西亚华语的书面传媒语体为语料，考察“动宾带宾”结构在新闻正文与标题的使用情况。调查发现该结构表现出三个较为显著的特点：（一）在 192 个动宾复合词中，近九成的复合词出现带宾语的用例，这说明马来西亚华语中“动宾带宾”现象极为常见、大多数动宾复合词具有及物用法；（二）动宾复合词的及物率与其宾语的句法结构类型的多元程度不存在正向关联；（三）“动宾带宾”结构的宾语在音节数量、定语和中心语的相互语序、语码夹杂等方面表现出一些独有特点。再者，本研究亦对比“动宾带宾”在新闻正文与标题的异同，当中显著的差异包括：（一）动宾复合词在正文的及物率低于标题；（二）正文中带宾的 VO 数量多于标题；（三）正文中宾语功能类型的受限程度低于标题。此外，本文亦比较了“动宾带宾”在马来西亚华语、大陆普通话、台湾国语中的异同。本文主要发现：（一）马来西亚华语的“动宾带宾”的使用率最高，依次为台湾国语、中国大陆普通话；（二）在三个汉语变体中，“动宾带宾”的宾语在马来西亚华语具有更多元的形式，包括单音节宾语、定语后置于中心语的宾语、语码夹杂的宾语，但普通话和台湾国语并未发现这些类型的宾语。本文认为，马来西亚华语的“动宾带宾”与其他汉语变体地区出现上述差异是马来西亚的语言环境所致，马来西亚华语较大程度上受到古汉语、南方方言、英语的影响。“Verb-object compound + object” (VO1+O2 construction) is a special grammatical phenomenon in Chinese. Current research on this structure primarily focuses on Mainland Mandarin Chinese, with little research on other Chinese varieties. This thesis investigates the use of VO1+O2 in both the body and headlines of news articles utilizing a corpus of written media in Malaysia Mandarin Chinese. The study uncovers three significant characteristics of VO1+O2: (a) among 192 VO compounds, nearly 90% of them are found to take objects, which indicates that the VO1+O2 is highly prevalent in Malaysia Mandarin Chinese, with most VO compounds being transitive; (b) there is no positive correlation between the transitivity of VO compounds and the diversity of syntactic structures of the object; (c) the object within the VO1+O2 is characterized by distinctive features, encompassing the number of syllables, the word order of modifiers and heads, and codemixing. Furthermore, the study also contrasts the similarities and discrepancies of VO1+O2 between news body and headline. The noteworthy differences comprise: (a) in contrast to the headline, the transitivity of VO compound is lower in the news body; (b) compared to the headline, there are more VO compounds capable of being followed by another object in the news body; (c) the limitations on object types are less in the news body than in the headline. Additionally, this paper also compares the commonalities and disparities of VO1+O2 in Malaysia Mandarin Chinese, Mainland Mandarin Chinese and Taiwan Mandarin Chinese. The main findings include: (a) the highest usage rate of VO1+O2 is observed in Malaysia Mandarin Chinese, followed by Taiwan Mandarin Chinese and Mainland Mandarin Chinese, respectively; (b) among these three Chinese varieties, the object of VO1+O2 was found in more diverse forms in Malaysia Mandarin Chinese, including monosyllabic object, object with posthead modifiers object and object with code-mixing, which are not identified in Mainland Mandarin Chinese or Taiwan Mandarin Chinese. This paper concludes that the differences in VO1+O2 between Malaysia Mandarin Chinese with other Chinese varieties are attributed to the language environment in Malaysia, which is significantly influenced by Classical Chinese, Southern Chinese dialects, and English.